CURRENT SCENARIO AND RESOURCES FOR WRESTLERS AND THEIR PERFORMANCE IN HARYANA - Anjli; Pandey, Dharam Pani (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Background: Wrestling is the game which has been practiced since ancient times and it is one of the popular sports in India. This is an ongoing study in which all the Government approved wrestling academies in all 23 districts of Haryana has to cover. In this paper, 7 districts have discovered. The objectives of the study are to check the availability of services that are provided in the academies of Haryana with the special reference to physiotherapy services. Methods: All Government and Government approved academies of 7 districts of Haryana state were taken in the study and remaining 16 districts are yet to be covered. Survey method in the form of questionnaire is used to find out the current scenario and resources for wrestlers and their performance in Haryana state. Result: Majority of wrestlers say that there is no physiotherapist available during training sessions, only 9.5% of them say yes to physiotherapy services available during training sessions. Whereas injuries are most common in wrestling; So, physiotherapy services will definitely enhance the level as well as performance of Haryana wrestlers in world wide. Conclusion: Physiotherapy services are most important aspect in wrestling. If physiotherapy is added, it can enhance the performance as well as boost up their career.